The Impact of the Smash Training Method with the Ball Media on the Efficacy of Smash Punches during Volleyball Games among PBVSI Oku Timur Athletes - Jujur Gunawan Manullang; Satria Wijaya (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2023)
Objective. In this study, the issue at hand pertains to the suboptimal results of smash blows. Specifically, the practice method of utilizing smash drills with the medium of a ball on the hang, which can significantly contribute to smash blows, has not been implemented. This omission has led to a failure to maximize smash-blow outcomes. Materials and Methods. This research aims to investigate the impact of smash training and hanging ball media on the efficiency of volleyball smashes in male athletes of PBVSI OKU Timur. The research employed an experimental approach, utilizing a One Group Pre-test Post-test design, and statistical analysis to determine the correlation between the two variables under examination. The data was collected through a smash punch test, which measured the effectiveness of a smash punch in a volleyball game. The study population consisted of 12 male athletes participating in volleyball training at PBVSI OKU Timur. Results. After conducting an experimental analysis to measure the impact of smash training and hanging ball media on the efficiency of smash punches, a hypothesis was tested using the t-test. The results showed a t-count of 3.428 and a t-table of 1.782, indicating that the influence of the two factors was significant. In other words, the training and use of hanging ball media positively affected the results of smash punches. Conclusions. The study found that smash training with ball media hanging had a significant effect on the results of smash punches in volleyball games among athletes of PBVSI OKU Timur. Specifically, Ha was accepted and Ho was rejected, indicating that the training technique was effective in improving the athletes' performance.